The didactic approaches to teaching of pediatrics in the conditions of the credit-transfer system in the studying of english-speaking foreign students of medicine - Lezhenko, G. O.; Pashkova, O. E.; Sidorova, I. V.; Kraynya, H. V.; Леженко, Геннадій Олександрович; Пашкова, Олена Єгорівна; Сидорова, Ірина Володимирівна; Крайня, Ганна Вікторівна (ТДМУ, 2017)
The aim of the study – to analyze the personal experience of credit-transfer system for teaching students at the Department of Pediatrics and optimization of teaching methods to date. Materials and Methods. At work methods of analysis of literary sources and personal experience in conditions of the credit-transfer system in teaching of Pediatrics. Results and Discussion. To increase student’s interest we suggest giving them a possibility to receive extra discipline points on account of independent educational work and other kinds of student’s activities (preparation of library-research papers, reports and small reports on the lessons, which overstep the frames of compulsory knowledge minimum). Extra points are added to the general sum of points. Due to a big part of educational program is occupied for independent material studying, we increase the amount of visual material (such as multimedia materials, educational films). Grading of student’s level of preparation for practical lessons includes testing of their base knowledge, quiz control on particular lesson topic, oral test, knowledge and ability to perform specified by the program practical skills and abilities, that is work with sick people, interpretation of laboratory and auxiliary methods of examination, solving situational tasks, which help students to work off their clinic thinking skills. An important part of educational process is a creation of conditions for student’s knowledge self-examination, receiving moral satisfaction of understanding a certain topic and of being fluent in it. Pedagogical elements are also the goal of practical lesson: student has to learn to follow behavior rules, the doctor’s ethics principles and deontology next to the patient’s bed, master the ability to establish a psychological contact with the patient and his family, learn the feeling of professional responsibility to provide a qualified medical assistance in time and also adequate. Conclusions. In order to fully organize a practical-oriented teaching of Pediatrics for English-speaking foreign students, who study in “Medical” specialization, which would suit European standards, we need to increase the amount of visual material (multimedia materials, educational films). We need to include clinic-situational tasks, work with patients, interpretation of laboratory and auxiliary methods of examination, which will allow foreign students to use received fundamental knowledge in application aspect and in practical activities in future. It’s will help student’s motivation during discipline studying. In order to lift motivation for independent educational work in a certain discipline we need to unify the ability to receive extra points and other kinds of activities, in a way of creating an algorithm and terms for giving extra points to the general score. Мета дослідження – аналіз власного досвіду використання кредитно-модульної системи при навчанні студентів на кафедрі педіатрії та оптимізування методики викладання до сучасних вимог. Матеріали та методи дослідження. У роботі використано методи аналізу літературних джерел та власного досвіду роботи в умовах кредитно-модульної системи при викладанні педіатрії. Результати й обговорення. Для підвищення зацікавленості студентів ми пропонуємо надати можливість отримання додаткових балів з дисципліни за рахунок самостійної навчальної роботи та інших видів діяльності студентів (підготовка рефератів, доповідей та повідомлень на заняттях, що виходять за рамки обов’язкового мінімуму знань). Додаткові бали додаються до загальної кількості з дисципліни. У зв’язку з тим, що велика частина навчальної програми відводиться на самостійне вивчення матеріалу, ми збільшуємо кількість наочного матеріалу (мультимедійні матеріали, наукові фільми). Оцінювання підготовки студентів до практичних занять включає перевірку базових знань, тестовий контроль, усне опитування, вміння виконувати практичні навички та вміння, тобто роботу з хворими, інтерпретування лабораторних та допоміжнихметодів обстеження, вирішення ситуаційних задач, які допомагають студентам відпрацьовувати навички клінічного мислення. Важливим компонентом навчального процесу є створення умов самооцінки знань студента, одержання морального задоволення від розуміння теми та вільної орієнтації в ній. Метою практичного заняття також є виховні елементи: студент повинен навчитися дотримуватися правил поведінки, принципів лікарської етики та деонтології біля ліжка хворого, оволодіти вмінням встановлювати психологічний контакт із пацієнтом та його родиною, засвоїти почуття професійної відповідальності за своєчасність та адекватність надання кваліфікованої медичної допомоги. Висновки. Для повноцінної організації практично орієнтованого викладання педіатрії іноземним студентам, які навчаються англійською мовою за фахом “Лікувальна справа”, яке б відповідало європейським стандартам, необхідно збільшити кількість наочного матеріалу (мультимедійні матеріали, наукові фільми). У структуру практичного заняття включати клініко-ситуаційні задачі, роботу з хворими, інтерпретування лабораторних та допоміжних методів обстеження, які дозволять іноземним студентам застосувати отримані фундаментальні знання в прикладному аспекті й у практичній діяльності в майбутньому, що допоможе підвищити мотивацію студентів під час вивчення дисципліни. Для підвищення мотивації самостійної навчальної роботи з дисципліни необхідно уніфікувати можливість отримання додаткових балів за інші види діяльності, шляхом розробки алгоритму та вимог до надання додаткових балів до загального рейтингу.
Дидактичні підходи до викладання педіатрії в умовах кредитно-модульної системи при підготовці іноземних студентів, які навчаються англійською мовою за фахом "Лікувальна справа"
Keywords: Pediatrics; credit-transfer system; higher medical education (degree in medicine); педіатрія; кредитно-модульна система; вища медична освіта